1997
DOI: 10.1063/1.119262
|View full text |Cite
|
Sign up to set email alerts
|

Metal–oxide–semiconductor capacitors formed by oxidation of polycrystalline silicon on SiC

Abstract: A method to form SiO2/SiC metal–oxide–semiconductor structures by oxidation of a thin polycrystalline silicon (polysilicon) layer deposited on SiC is demonstrated. The oxidation time used is sufficient to oxidize all the polysilicon while short enough at 1050 °C to insure insignificant oxidation of the underlying SiC. Since the oxidation of SiC is highly anisotropic, this method allows uniform oxide formation on a nonplanar SiC surface. The SiO2/SiC interface quality is comparable to that obtained with thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
70
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 17 publications
1
70
0
Order By: Relevance
“…The presence of a third element, however, namely C, results in a wide range of phenomena that do not occur in the Si-SiO 2 system. In particular, oxidation of SiC entails the production of CO which effuses through the oxide [1,2]. Afanas'ev et al have suggested that carbon clusters at and near the interface form during oxidation [3,4], but the structure and dynamics of these clusters has not been established.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a third element, however, namely C, results in a wide range of phenomena that do not occur in the Si-SiO 2 system. In particular, oxidation of SiC entails the production of CO which effuses through the oxide [1,2]. Afanas'ev et al have suggested that carbon clusters at and near the interface form during oxidation [3,4], but the structure and dynamics of these clusters has not been established.…”
mentioning
confidence: 99%
“…We assume that the advancing interface during oxidation emits CO molecules, as found in Refs. [1] and [2], and explore the possible reactions that CO molecules can undergo in the SiO 2 matrix. A perfectly bonded network without any defects is first considered.…”
mentioning
confidence: 99%
“…This would correspond to a higher density of interface states and thus to lower mobility as observed in experiments. [1][2][3][4][5] On the other hand, for energies close to the valence-band edge the DOS could be higher or lower for 4H-SiC than for 6H-SiC. For example, if the 6H-SiC is terminated by the carbon atom labeled C͑2͒ ͑see Figs.…”
mentioning
confidence: 99%
“…However, the SiC-SiO 2 interface does not have the desirable properties that characterize the Si-SiO 2 interface: the electron mobility in 4H-SiC layers adjacent to the interface is about two orders of magnitude smaller than that in the bulk. [1][2][3][4][5] The density of states ͑DOS͒ at the interface between SiC and SiO 2 is found to be much higher than the corresponding DOS at the Si-SiO 2 interface. [1][2][3][4][5] Moreover, different polytypes show unusual mobilities with respect to their bulk counterparts.…”
mentioning
confidence: 99%
See 1 more Smart Citation